The Transient Response of Organic Electrochemical Transistors. Issue 5 (20th February 2022) - Paudel, Pushpa R.; Skowrons, Michael; Dahal, Drona; Radha Krishnan, Raj Kishen; Lüssem, Björn
Abstract: A fast response of organic electrochemical transistors (OECTs) to electrical or chemical changes is essential for a widespread acceptance of this technology. However, finding design rules for fast switching OECTs is complicated by the fact that current transient device models are highly simplified and rely on a 1D approximation of the device that neglects details of the ion and hole concentration inside the transistor channel. To improve the understanding of transient processes limiting the speed of OECTs, a 2D drift‐diffusion model is presented and experimentally validated. It is shown that switching is strongly influenced by lateral ion currents that are neglected in previous models. A consistent treatment of these currents leads to a dependency of the time constants on the applied drain potential and a complex dependency of the response time constants on the detailed device geometry. In addition to an improved understanding of the transient response of OECTs, the results discussed here highlight the challenges in properly characterizing switching time constants of OECTs, and reinforce the necessity to ensure that switching is measured between two steady‐state conditions, and not between transient states. Abstract : A fast response of organic electrochemical transistors to changing environmental conditions is essential for their widespread use as sensors. Here, a 2D drift–diffusion model is presented to gain a better understanding of transient processes limiting the speed of OECTs. It is shown that the switching is strongly influenced by lateral ion currents which in turn depends on the biasing conditions, and the detailed geometry.